Associations between menopause, cardiac remodeling, and diastolic function: the CARDIA study. Issue 10 (14th October 2021) - Ying, Wendy; Post, Wendy S.; Michos, Erin D.; Subramanya, Vinita; Ndumele, Chiadi E.; Ouyang, Pamela; Ambale-Venkatesh, Bharath; Doria De Vasconcellos, Henrique; Nwabuo, Chike C.; Schreiner, Pamela J.; Lewis, Cora E.; Reis, Jared; et al.
Abstract : Supplemental Digital Content is available in the text Abstract: Objectives: Heart failure with preserved ejection fraction (HFpEF) affects more women than men. Menopause may influence HFpEF development in women. We assessed cross-sectional and longitudinal associations between menopause and echocardiographic measures of left ventricular (LV) function and cardiac remodeling. Methods: We studied 1, 723 women with available echo data from at least two of: year 5 (Y5) (1990-1991), Y25 (2010-2011), or Y30 (2015-2016) in the Coronary Artery Risk Development in Young Adults study. Cardiac structure and function were measured using 2D and Doppler echocardiography. Cross-sectional associations between menopausal status and repeated echo measures at Y25 and Y30 were analyzed using linear mixed models. Two-segmented models were used to compare longitudinal changes in echocardiographic measures in the premenopausal period to changes in the postmenopausal period. Results: Mean ± SD age (years) at enrollment was 27 ± 3 in those with menopause by Y25, 25 ± 3 in those with menopause between Y25 and Y30, and 21 ± 3 in those premenopausal at Y30. There were no significant differences in race, body mass index, systolic blood pressure, or diabetes between the groups. Postmenopausal women had higher early diastolic mitral inflow ( E ) to annular ( e ') velocity ratio than premenopausal after adjusting for demographics and risk factors ( P  < 0.05). Menopause was associated with relative increases in the rates of change in LV mass and left atrial volume, even after adjustment. Change in E / e ' ratio was similar before and after menopause. Conclusions: Menopause is associated cross-sectionally with worse diastolic function and longitudinally with adverse LV and left atrial remodeling. This may contribute to the increased HFpEF risk in postmenopausal women. Abstract : : Video Summary: http://links.lww.com/MENO/A787 .